Psychometric Properties of the EQ-5D for the Assessment of Health-Related Quality of Life in the Population of Middle-Old and Oldest-Old Persons: Study Protocol for a Systematic Review - Gottschalk, Sophie; König, Hans-Helmut; Nejad, Mona; Dams, Judith (Frontiers in Public Health, 2020)
Introduction: Health care interventions for middle-old and oldest-old individuals (75 years or older) are often economically evaluated using the EuroQol questionnaire (EQ-5D) to measure health-related quality of life. However, the psychometric performance of the EQ-5D in this population has been questioned, as it probably does not adequately capture relevant aspects of quality of life in the older population. Because the results of economic evaluations using the EQ-5D often guide decision-makers, it is important to know whether the EQ-5D has satisfactory psychometric properties in the middle-old and oldest-old population. Therefore, studies assessing the psychometric properties of the EQ-5D in this population should be synthesized by a systematic review. Methods and Analysis: A systematic review of studies providing empirical evidence of reliability, validity, and/or responsiveness of the EQ-5D in a sample with a mean age ≥75 years will be conducted. The databases PubMed, Web of Science, and EconLit will be searched. In addition, reference lists of included studies will be hand-searched. Two independent reviewers will select studies and assess their risk of bias with the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) Risk of Bias checklist. Relevant data will be extracted by one reviewer and cross-checked by a second reviewer. Potential disagreements in any phase will be resolved through discussion with a third person. The guidelines for systematic reviews of measurement properties proposed by the COSMIN group, including criteria of good measurement properties, will guide the synthesis and interpretation of the results. Discussion: The review's results could facilitate the making of recommendations for the use of the EQ-5D in a population of middle-old and oldest-old people and thereby being of interest for decision-makers or for researchers designing new intervention studies for older people. Heterogeneity of individual studies regarding the population under study could limit the possibility of making a synthesized statement on the appropriateness of the EQ-5D for the middle-old to oldest-old population.